Using Virtual Reality in Forensic Physics Education - Eruygun, Orkun; Yalçın Sarıbey, Aylin (The Bulletin of Legal Medicine, 2025)
Objective: This study aimed to develop a virtual reality tool using 3D visualization technology for ballistic pendulum experiment to be used in basic ballistics education. Methods: The virtual experiment development process was carried out in three stages; (i) scientific preparation, (ii) graphic design and 3D modeling and (iii) software development. The “Ballistic Pendulum Experiment”, which aims to determine the exit velocity of the bullet core from the barrel, was developed to allow users to perform measurements and calculations by changing the initial parameters of the experiment with 7 different projectile options. Results: The software was run by selecting 9x19 Parabellum projectile and test integrations were performed. In the experiment, a 5.7 g bullet core was lodged into a 4 kg pendulum block at a distance of 1.3 meters from the pivot point by making a central fully flexible collision. Neglecting angular momentum and considering only linear momentum, the exit velocity of the bullet from the barrel was calculated as 652 m/s, a difference of 55 m/s from the reference value indicating the ballistic performance of the projectile (597 m/s). Conclusion: A dynamic experimental environment was developed with VR technology, based on 3D models and scientific algorithms, where each student can obtain different results with their own parameter changes. In this way, an alternative solution was offered to the difficulties encountered in issues such as security reasons, official procedures and permission legislation for the use of weapons, weapon supply, and the lack of physical laboratories with sufficient number and equipment.